Parents' Stress and Children's Psychological Problems in Families Facing the COVID-19 Outbreak in Italy - Spinelli, Maria; Lionetti, Francesca; Pastore, Massimiliano; Fasolo, Mirco (Frontiers in Psychology, 2020)
Objectives: The present study aimed to explore the effect of risk factors associated with the COVID-19 outbreak experience on parents' and children's well-being. Methods: Parents of children aged between 2- and 14-years-old completed an online survey reporting their home environment conditions, any relation they had to the pandemic consequences, their difficulties experienced due to the quarantine, their perception of individual and parent-child dyadic stress, and their children's emotional and behavioral problems. Results: Results showed that the perception of the difficulty of quarantine is a crucial factor that undermines both parents' and children's well-being. Quarantine's impact on children's behavioral and emotional problems is mediated by parent's individual and dyadic stress, with a stronger effect from the latter. Parents who reported more difficulties in dealing with quarantine show more stress. This, in turn, increases the children's problems. Living in a more at-risk area, the quality of the home environment, or the relation they have with the pandemic consequences, do not have an effect on families' well-being. Conclusions: Dealing with quarantine is a particularly stressful experience for parents who must balance personal life, work, and raising children, being left alone without other resources. This situation puts parents at a higher risk of experiencing distress, potentially impairing their ability to be supportive caregivers. The lack of support these children receive in such a difficult moment may be the reason for their more pronounced psychological symptoms. Policies should take into consideration the implications of the lockdown for families' mental health, and supportive interventions for the immediate and for the future should be promoted.